A novel activated flux coating method for reducing fumes at breathing zone concentration (BZC) for the stellite hardfacing process. (2021) - Raajesh Kannan, R.K.; Sivapirakasam, S.P.; Vishnu, B.R.; Rahul, M.; Balasubramanian, K.R.; Mohan, Sreejith
Abstract: Hardfacing is a popular welding process in which a substrate material is overlaid with additional material to impart wear and corrosion resistant. Since there are certain occupational and environmental hazards associated with this process, an environmental friendly hardfacing process was developed by coating an activated flux of alumina precursor on the base material. By this innovative approach, the fume formation at BZC was reduced up to 60% compared to conventional methods of stellite hardfacing. The finest interaction effects of process parameters which favoured the maximum reduction of fumes emission at breathing zone concentration was analysed using Response Surface Methodology of Design of Experiments (DoE).